Aiming for a holistic integrated service for men diagnosed with prostate cancer – Definitions of standards and skill sets for nurses and allied healthcare professionals. (August 2017) - Lamb, Alastair D.; Thompson, Sue; Kinsella, Netty; Gerbitz, Ingmar; Chapman, Elaine; Putt, Lisa; Bennett, Sophie; Thankappannair, Vineetha; Geoghegan, Lisa; Wright, Naomi; Stirton-Croft, Alison; Nixon, Penny; et al.
Abstract: Purpose: To establish a comprehensive set of recommendations for the service structure and skill set of nurses and allied healthcare professionals in prostate cancer care. Methods: Using components of formal consensus methodology, a 30-member multidisciplinary panel produced 53 items for discussion relating to the provision of care for prostate cancer patients by specialist nurses and allied healthcare professionals. Items were developed by two rounds of email correspondence in which, first, items were generated and, second, items refined to form the basis of a consensus meeting which constituted the third round of review. The fourth and final round was an email review of the consensus output. Results: The panel agreed on 33 items that were appropriate for recommendations to be made. These items were grouped under categories of "Environment" and "Patient Pathway" and included comments on training, leadership, communication and quality assessment as well as specific items related to prostate diagnosis clinics, radical treatment clinics and follow-up survivor groups. Conclusions: Specialist nurses and allied healthcare professionals play a vital role alongside urologists and oncologists to provide care to men with prostate cancer and their families. We present a set of standards and consensus recommendations for the roles and skill-set required for these practitioners to provide gold-standard prostate cancer care. These recommendations could form the basis for development of comprehensive integrated prostate cancer pathways in prostate cancer centres as well as providing guidance for any units treating men with prostate cancer. Highlights: First consensus report on provision of gold-standard prostate cancer care by nursing & AHPs in dedicated prostate cancer unit. 33 individuals: patients, nurses, physiotherapists, radiotherapists, psychologists, researchers, oncologists and surgeons. The process involved several rounds of review and centred on a face-to-face round-table meeting. We cover the entire prostate cancer care pathway from first clinic visit to end-stage care. General aspects of care provision such as leadership styles and communication are discussed. These recommendations could form a model for similar care to be provided in other institutions.